1963
DOI: 10.1111/j.1365-4362.1963.tb06142.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsporum Infection in Rio Grande Do Sul (Brazil)

Abstract: Summary One hundred seventynine cases of human tinea infections caused by various species of Microsporum were seen by the author in Rio Grande do Sul, Brazil, from 1957 to 1962; 175 cases were due to M. canis and four to M. gypseum. The majority of patients were Caucasian children up to five years of age; the incidence diminished thereafter. Among adult females, however, infections were not uncommon. Multiple cases within families were common; multiple lesions were frequent. All of the patients lived in urban … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1966
1966
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Our sample of tinea capitis in children was characterized by higher frequency between 0-5 years (66.0%) and in males (62.5%). However, in the literature, there are reports with preponderance in the ages 0-5 26,29 , 1-5 52 , 5-10 23 , 6-12 9,45,47 and 7-12 15 and male predominance 15,23,26,47,54 . These findings can be explained by several variables: short hairs making easier the implantation of spores 23 , dressing with petrolatum or other oils acting as an adherent for the arthroconidium 44 and cosmetic oils inhibiting the dermatophyte colonization 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Our sample of tinea capitis in children was characterized by higher frequency between 0-5 years (66.0%) and in males (62.5%). However, in the literature, there are reports with preponderance in the ages 0-5 26,29 , 1-5 52 , 5-10 23 , 6-12 9,45,47 and 7-12 15 and male predominance 15,23,26,47,54 . These findings can be explained by several variables: short hairs making easier the implantation of spores 23 , dressing with petrolatum or other oils acting as an adherent for the arthroconidium 44 and cosmetic oils inhibiting the dermatophyte colonization 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Brown (1966) (Wong and Chan, 1968). Both Georsi, Hand and Menges (1956) and Londero (1963) have found M. canis restricted to urban areas, being rare or absent in rural areas. The seasonal distribution of animal and human ringworms due to M. canis in the Dunedin area follow a similar pattern with peaks in autumn and winter montlis (March-August) and a low in the spring and early summer (September-December).…”
Section: Discussionmentioning
confidence: 99%
“…The age and sex distribution of M. canis ringworms in man and animals needs little comment. Various authors have demonstrated the affinity of this dermatophyte for children and kittens (Marples, 1951;Georg, 1960;Londero, 1963;Keep, 1963). Earlier in New Zealand (Marples, 1951) and in Brazil (Londero, 1963) it had been demonstrated that in the yonnger age gronps, infection was more common in males than females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Central America it is replaced by T. tonsurans (Gonzalez-Ochoa & Gonzalez-Mendoza, 1960;Gonzalez-Ochoa & Victoria, 1974). The most extensive survey has been carried out in Brazil (Londero, 1962(Londero, , 1963(Londero, , 1964 mainly in the south of the country. M. canis is the dominant agent of tinea capitis and tinea corporis in urban areas: a feature of the survey was the large number of cases recorded in children under five.…”
Section: Europementioning
confidence: 99%